Falls in the Elderly: A Multidisciplinary Approach to Screening and Evaluation of Falls in Resident Primary Care Clinics - Jennifer Lom; Jonathan Flacker; Rachael Walton-Mouw (Association of American Medical Colleges, 2015)
Abstract Introduction Internal medicine residents working in their primary care clinics have an increasing number of geriatric patients for whom they are providing care. Unfortunately, many residents do not have a geriatric medicine rotation, or what they do have is either so brief or comes so late in training (as in our program) that there is not a positive impact on the patients they care for. Lack of confidence in screening their geriatric patients for falls as well as limited education can lead to many missed opportunities to help prevent falls. Methods This workshop is highly interactive and designed to take 1.5 hours, although it can be modified to fit in an hour. It is intended to be delivered in a small-group setting to approximately 10-15 learners. Results We assessed resident attitudes and confidence on addressing the topic of falls with their patients with a premodule survey. Questions were rated using a 5-point Likert scale. Residents rated how confident they felt in their ability to identify an older patient at risk for falls (3.43), in performing a fall screening on their patients (3.05), in performing a comprehensive falls history (3.28), in performing a comprehensive falls physical exam (2.80), and in prescribing evidence-based interventions to patients with falls (2.58), as well as if they believed falls were an important problem in the elderly population (4.58). Discussion This was the first year incorporating this module into the ambulatory block and the responses were overwhelmingly positive. In terms of future directions we plan to distribute this to residents and students in other disciplines (family medicine, nursing, physical therapy). Data will be collected throughout this year and future years to determine whether or not the residents' self-efficacy increased and was sustainable after their ambulatory module.